Influencing Factors on the Actual Usage of Mobile Phone Banking in the Shari'ah Banks: A Survey in Palembang City, Indonesia - Chandra Zaki Maulana; Yuyus Suryana; Dwi Kartini; Erie Febrian (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2019)
This research was developed from a study conducted by Talukder, Quazi and Sathye in 2014 whom were tried to discover mobile phone banking usage behavior of banks customers in Canberra, Australia. A research model was set to find the relationship between independent and dependent variables. Independent variables consisted of five variables, namely, Perceived Usefulness (PU), Perceived Ease of Use (PEU), Trust (T), Social Influence (SI) and System Quality (SQ), whilst the dependent variable is Actual Usage (AU) of Mobile banking in the Shari’ah banks. Thus, making this research a multiple regression analysis. A survey was conducted by distributing questionnaires to gather primary data from 126 respondents of Shari’ah banks customers in Palembang City, South Sumatra Province, Indonesia. The findings show evidence that there are positive and significant relationship between all independent variables and the dependent variable. As such variable with the highest impact is PEU (30,3%) whilst the lowest is SI (18%) meaning that perceived ease of use amongst customers of Shari’ah banks in Palembang City gave the highest impact on their actual usage of mobile banking, compared to social influence, which is lower. Therefore, it is recommended that Shari’ah banks in this city should consider to put more attention in to providing their customers with a mobile banking application which is easy to use as well as keeping it up to date with the needs of the customers. As an implication to the providers, financial institutions can capitalize on the finding of this research to enhance the ease of use of their application on mobile banking.